2001
DOI: 10.2105/ajph.91.8.1310
|View full text |Cite
|
Sign up to set email alerts
|

Brief Intervention for Heavy-Drinking College Students: 4-Year Follow-Up and Natural History

Abstract: Brief individual preventive interventions for high-risk college drinkers can achieve long-term benefits even in the context of maturational trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
309
2
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(337 citation statements)
references
References 33 publications
20
309
2
6
Order By: Relevance
“…These improvements exceeded the reductions associated with the TLFB/control condition. Our findings add to the growing literature documenting the efficacy of individually-administered BMIs for at-risk college drinkers (Baer, Kivlahan, Blume, McKnight, & Marlatt, 2001;Borsari & Carey, 2000;Murphy et al, 2004;Murphy et al, 2001). Importantly, this study demonstrated differential improvement compared to two comparison conditions, a standard assessment control and an active TLFB/control condition.…”
Section: Discussionsupporting
confidence: 64%
“…These improvements exceeded the reductions associated with the TLFB/control condition. Our findings add to the growing literature documenting the efficacy of individually-administered BMIs for at-risk college drinkers (Baer, Kivlahan, Blume, McKnight, & Marlatt, 2001;Borsari & Carey, 2000;Murphy et al, 2004;Murphy et al, 2001). Importantly, this study demonstrated differential improvement compared to two comparison conditions, a standard assessment control and an active TLFB/control condition.…”
Section: Discussionsupporting
confidence: 64%
“…To retain as many children as possible who met our eligibility criteria for inclusion in our analyses (i.e., at least age 7 by the time of the 2000 assessment), we used MI (Baer, Kivlahan, Blume, McKnight, & Marlatt, 2001;Rubin, 1987;Schafer, 1997). MI replaces missing values with predictions based on all the other information observed in the study.…”
Section: Missing Data and Multiple Imputationmentioning
confidence: 99%
“…This includes a lack of effect on reduced initiation of substance use, and there is also an absence of secondary prevention effects, as would be expected on the basis of prior studies, particularly on alcohol consumption (Baer et al 2001;McCambridge & Strang, 2004;Hettema et al 2005;Gray et al, 2005). What between-group differences there are suggest the possible effectiveness of the classroom-based Drug Awareness discussion on the prevalence of cannabis use.…”
Section: Discussionmentioning
confidence: 94%
“…We believe it is more likely that neither intervention has been effective in changing the behaviour of the study participants, and if this is proven to be correct, there is an important implication to be considered: Combining pursuit of primary and secondary prevention effects has apparently served to blunt the impact upon existing substance use that should be expected on the basis of previous secondary prevention studies, most notably upon alcohol consumption, for which there is the largest and most positive evidence-base (Baer et al 2001;Hettema et al 2005;Gray et al, 2005). It seems likely that in trying to prevent young people from doing something which they are not, we have unfortunately hampered the possibility of healthy influence of their current behaviour.…”
Section: Discussionmentioning
confidence: 99%